Analisis Kesulitan Peserta Didik dalam Pemecahan Masalah Matematis pada Soal Cerita di Sekolah Dasar - Siti Aisyah; Salmaini Safitri Syam; Chandra Chandra (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Mathematics is often referred to as a field of knowledge developed through logical reasoning and is considered essential in everyday life, particularly in problem-solving. One effective way to apply problem-solving skills in mathematics education is through the use of word problems. This study aims to explore and analyze the various obstacles students encounter when solving mathematical word problems. The research employs a descriptive qualitative approach, with data collection methods including tests, interviews, and a project involving the construction of a staircase using standard units of length. The subjects of the study were four third-grade elementary school students in Batusangkar who had previously studied standard units of length. The findings reveal that students faced a range of difficulties, such as challenges in understanding the problems, failure to organize solution steps systematically, and limited comprehension of the concept of standard measurement units. Additionally, a lack of interest in learning was found to negatively impact students’ ability to solve word problems. Therefore, conceptual understanding and increased motivation to learn are crucial factors in enhancing students’ mathematical problem-solving abilities.